A 3D-DEM investigation of the mechanism of arching within geosynthetic-reinforced piled embankment. (15th March 2020) - Badakhshan, E.; Noorzad, A.; Bouazza, A.; Zameni, S.; King, L.
Abstract: In this paper, 3D discrete element method (DEM) simulations are proposed to explore the mechanism of arching within geosynthetic-reinforced and unreinforced piled embankments. Comparisons are made between the numerical and the measured data of IFSTTAR centrifuge tests with regards to efficiency response, volumetric deformation and displacement characteristics to verify the DEM. Resulted show that, considering the kinematic of the arching process, discrete nature of the utilized numerical model for soil allows a good description of the evolution of the load recovery stage and contact forces within the granular material. Also, simulation results confirm that the load recovery phase can take place in geosynthetic-reinforced cases when geosynthetic layer has not enough stiffness to support the arch load which causes the geosynthetic destroy prior to reaching maximum efficiency. Further, the numerical investigation is extended to examine the effects of the vertical spacing of the second layer of the reinforcement on efficient and differential settlement. Findings indicated that, when second layer of the reinforcement is used, there is an optimum vertical spacing for which the lowest value of the differential settlement is reached. In addition, analyses indicate that increasing reinforcement stiffness has a lower influence on achieving the maximum efficiency in the lower settlement than increasing the number of reinforcement layers, if the second layer of reinforcement is placed within an effective height range.